Memory Is Not About the Past - Chahine, Anne (Journal of Anthropological Films, 2021)
The short documentary "Memory Is Not About the Past" aims to understand how members of the so-called Third Generation East, individuals who experienced the fall of the Berlin Wall as children or young adolescents, remember East Germany 26 years after reunification. The field of research is the city of Berlin and all its former East German districts. Walking, as a performative practice, is at the centre of this ethnographic journey. With every step, the individuals reclaim their childhood neighbourhood and, at the same time, position themselves in the present. The urban space functions as a sounding board of the individual's inner thoughts and embodied experiences and is closely intertwined with stories of former communal solidarity, social change and an underlying level of estrangement from these areas.